Cytotoxic and Antiproliferative Effects of Gynura divaricata Ethanolic Extract on HCT-116 Colorectal Cancer Cells In Vitro - Putri Rifai, Fauziah Novita; Hidayah, Nurul; Sakinah, Feby Nur; Adityani, Resanti (International Journal of Cell and Biomedical Science, 2024)
Background: Colorectal cancer is a major cause of cancer-related morbidity and mortality worldwide. The limitations of conventional treatments such as chemotherapy and radiotherapy have driven the search for alternative therapies with fewer side effects. Objective: This study aimed to investigate the cytotoxic effects of Gynura divaricata extract on HCT-116 colorectal cancer cells and evaluate its potential as a complementary anticancer agent. Methods: Gynura divaricata was extracted using ethanol through a maceration process. HCT-116 cells were cultured and treated with various concentrations of the extract. Cell viability was measured using the MTT assay, and the IC50 value was calculated through linear regression analysis. Results: Treatment with Gynura divaricata extract resulted in a dose-dependent decrease in cell viability. The IC50 value was determined to be 62.09 µg/mL, indicating significant cytotoxic activity against HCT-116 cells. Conclusion: Gynura divaricata exhibits potential as an alternative or adjunctive therapy for colorectal cancer due to its ability to reduce cancer cell viability.